2017
DOI: 10.1111/epi.13890
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam does not modulate ionotropic channels activated by glutamate, γ‐aminobutyric acid, and glycine in hippocampal neurons

Abstract: Brivaracetam (BRV) is a selective, high-affinity ligand for synaptic vesicle protein 2A (SV2A), recently approved as adjunctive treatment for drug-refractory partial-onset seizures in adults. BRV binds SV2A with higher affinity than levetiracetam (LEV), and was shown to have a differential interaction with SV2A. Because LEV was reported to interact with multiple excitatory and inhibitory ligand-gated ion channels and that may impact its pharmacological profile, we were interested in determining whether BRV dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Subjects received a single oral dose of CBZ, BRV, or TGB in a double‐blinded, randomized, placebo‐controlled crossover design. The study was exploratory but, given the previous pharmaco‐TMS‐EEG data, we expected suppression of the P180 under CBZ and, possibly, an increase of N45 under BRV, although the detailed modes of action of BRV and levetiracetam are different, with levetiracetam but not BRV showing relevant inhibitory action on glutamatergic neurotransmission through AMPA and NMDA receptors (Lee, Chen, & Liou, ; Niespodziany et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…Subjects received a single oral dose of CBZ, BRV, or TGB in a double‐blinded, randomized, placebo‐controlled crossover design. The study was exploratory but, given the previous pharmaco‐TMS‐EEG data, we expected suppression of the P180 under CBZ and, possibly, an increase of N45 under BRV, although the detailed modes of action of BRV and levetiracetam are different, with levetiracetam but not BRV showing relevant inhibitory action on glutamatergic neurotransmission through AMPA and NMDA receptors (Lee, Chen, & Liou, ; Niespodziany et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…The high rate of AB with LEV may not necessarily be related to SV2A, since it has been suggested that BRV, which has a 15–30 times higher affinity to SV2A than LEV, is associated with a lower incidence of AB than LEV [6, 22, 23, 95]. Interestingly, it seems that BRV does not modulate NMDA, AMPA, or kainate receptors [96, 97]. These findings suggest that LEV's negative modulating effect on AMPA receptors contributes to increased AB.…”
Section: Possible Neuropharmacological Mechanisms Of Aed-induced Amentioning
confidence: 99%
“…This group carries the major burden of epilepsy, with increased rates of cognitive and behavioral problems, comorbidities, and reduced quality of life. [3][4][5] This mechanistic divergence between the two may explain the differences in outcomes observed in clinical trials. 2 The two AEDs bind to different sites on SV2A, and at therapeutically relevant concentrations, BRV has no effect on ligand-gated receptors or voltage-gated potassium and calcium channels.…”
Section: Introductionmentioning
confidence: 99%
“…2 The two AEDs bind to different sites on SV2A, and at therapeutically relevant concentrations, BRV has no effect on ligand-gated receptors or voltage-gated potassium and calcium channels. [3][4][5] This mechanistic divergence between the two may explain the differences in outcomes observed in clinical trials.…”
Section: Introductionmentioning
confidence: 99%